Pengaruh Karakteristik Komite Audit Terhadap Audit Report Lag - Ihsanul Fakri; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to examine the effect of audit committee independence, audit committee expertise, frequency of audit committee meetings, and the size of the audit committee on audit report lag. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. The research sample was determined using the purposive sampling method with a total sample of 87 companies. The data used is secondary data from the company's annual report. The analytical method used is multiple linear regression analysis. The results showed that the size of the audit committee had a negative effect on audit report lag, while the independence of the audit committee, audit committee expertise, and frequency of audit committee meetings did not affect on audit report lag.